Verifikasi Sensor Termokopel pada Furnace untuk Meningkatkan Akurasi Pemantauan Suhu di PT Krakatau Baja Konstruksi - Saepullah, M Zaiz; Aribowo, Didik (Universitas Batanghari Jambi, 2025)
Accurate temperature monitoring in the furnace is an important element in the processing of steel metals at PT Krakatau Baja Construction. Type S thermocouple sensors are used to measure temperature by converting temperature changes into voltage signals. However, to ensure the accuracy of the readings, thermocouple performance verification is carried out periodically. This research aims to verify thermocouples in several furnace zones to increase the accuracy of temperature data in the Human Machine Interface (HMI) system. The verification process uses the Fluke 17 B+ tool and Universal Transmitter PR4116. The measurement results are compared with the reference table and HMI readings before and after verification. The results show that all thermocouples function well with the largest deviation of 23°C in Zone 2A before adjustment and the smallest deviation of 1°C in Zone 1. Verification succeeded in reducing the deviation, ensuring the reliability of the measurement system. This research confirms the importance of thermocouple verification to improve production efficiency and product quality, with recommendations for regular evaluation of the HMI system and temperature measurements.